ANALISIS PENERAPAN KURIKULUM MADRASAH 2019: KAJIAN BUKU TEKS BINA FIQIH KELAS V SD/MI - Amarullah, Muhamad; Firdaus, Iqlima; Jannah, Mifthaul; Salamah, Huri; Nopasari, Dewi (Cahaya Ilmu Bangsa Institute, 2025)
Textbooks have an important role in the learning process both for students as a source of learning materials and for teachers as teaching guidelines. This study aims to evaluate the textbook